Cordilleran Ice Sheet early deglaciation inferred from evolution of Late‐Pleistocene glacial Lake Dzulh Stun in east‐central British Columbia, Canada - Brendan G. N. Miller; John J. Clague; Andrée Blais‐Stevens (Journal of Quaternary Science, 2026)
We document the early decay of the Late‐Pleistocene Cordilleran Ice Sheet in the central portion of the Rocky and Cariboo Mountains and the Rocky Mountain Trench in east‐central British Columbia. Glacial lakes impounded at the eastern margin of the ice sheet occupied watersheds on the west flank of the central Rocky Mountains, leaving extensive glaciolacustrine deposits and shorelines. Some of the lakes overflowed across high divides onto the westernmost Interior Plains. These lakes expanded westward and eventually coalesced to form glacial Lake Dzulh Stun, which grew to occupy ~400 km of the Rocky Mountain Trench and extended farther west into the adjacent Cariboo Mountains. Meltwater from the margin of the ice sheet located in the central Cariboo Mountains crossed the crest of the range in places and flowed into this lake. At this time, high elevations on the east side of the Cariboo Mountains were ice‐free, while major cross‐cutting valleys remained obstructed by ice. The lake drained to the north along the Parsnip River valley, through the Rocky Mountains and onto the Interior Plains, accompanied by an ~400 m (1213–808 m ASL) lowering in its level. These events occurred during perhaps a millennium within the period 13–14.5 ka before present.